Gender and geographic representation in editorial boards of education journals - Xue, Yan; Xu, Quan (Frontiers in Psychology, 2024)
Background Previous studies have examined the gender and geographic diversity within editorial boards across various academic disciplines, excluding the field of education. Thus, the purpose of this study was to address this gap by investigating the extent of gender and geographic disparity within the editorial boards of education journals. Methods The selection of top five education journals from each quartile (Q1–Q4) was performed based on Clarivate Analytics’ Journal Citation Reports (JCR) 2021 within the category of “Education & Educational Research.” The information of editors was collected through online sources. Results Overall, female editors accounted for 17 out of the 29 editors-in-chief (58.62%), 36 out of the 64 deputy/associate editors (56.25%), 378 out of the 728 editorial/advisory board members (51.92%) and 15 out of the 28 other types of editors (53.57%). There was no significant association between the impact factor (IF) and the proportion of female editors (Pearson’s r = −0.095, p = 0.689). The United States had the highest number of editors (n = 459, 54.06%), followed by the United Kingdom (n = 98, 11.54%), Australia (n = 63, 7.42%), China (n = 29, 3.42%), Germany (n = 25, 2.94%), and Canada (n = 22, 2.59%). Notably, the majority of the included editors were from developed countries (n = 794, 93.52%), while editors from developing countries constituted a significantly smaller proportion (n = 55, 6.48%). Conclusion Editorial boards of education journals exhibit reasonable gender diversity than other disciplines, though still fall short when considering the proportion of women in the discipline. Besides, obvious geographical disparity was observed among editorial boards of education journals. There was a notable lack of representation of researchers associated with institutions from developing countries on the editorial boards of education journals. While maintaining sufficient gender diversity, it is imperative to enhance the geographical diversity in these journals, ensuring a more equitable number of positions to individuals from these underrepresented groups.